Takhrij and Syarah Hadith of Chemistry: Fermented Fruit Juice Into Heady - Putri Widia Mukti; Salis Abdalah Hatami; Soni Setiadji; Dadang Kahmad; Tatang Zakaria (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad Saw. about the nabidz feeling. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The result and discussion of this research is that the nabidz juice is prohibited from being consumed by the Prophet because the nabidz juice has produced alcohol. The conclusion of this research is takhrij and syarah hadith of the Prophet Muhammad Saw. about nabidz juice with chemical analysis has a relationship, where the alcohol produced from the fruit sugar content can be intoxicating and harmful to the body if consumed in excess.